Nutritional Composition, Mineral Profiling, In Vitro Antioxidant, Antibacterial and Enzyme Inhibitory Properties of Selected Indian Guava Cultivars Leaf Extract - Moses Sam Arul Raj; Singamoorthy Amalraj; Saud Alarifi; Mohan G. Kalaskar; Rupesh Chikhale; Veerasamy Pushparaj Santhi; Shailendra Gurav; Muniappan Ayyanar (MDPI AG, 2023)
Psidium guajava L. is a small evergreen tree known for its magnificent medicinal and nutritional value. This study aimed to evaluate the nutritional profile and in vitro pharmacological potentialities of the different leaf extracts of four cultivars of Psidium guajava namely Surka chitti, Allahabad safeda, Karela, and Lucknow-49. The standard procedures of the Association of Official Analytical Chemists (AOAC) were followed to carry out the nutritional analysis and all of the cultivars recorded the presence of elements at a nominal range. The highest presence of phenols (125.77 mg GAE/g) and flavonoids (92.38 mg QE/g) in the methanolic leaf extract of the Karela cultivar was recorded. A wide range of minerals such as sodium, phosphorus, magnesium, zinc, and boron were recorded with a higher percentage in the Karela cultivar of Psidium guajava. In the enzyme inhibitory assays, Allahabad safeda showed potential inhibition with an IC50 of 113.31 ± 1.07, 98.2 ± 0.66 and 95.73 ± 0.39 μg/mL in α-amylase, α-glucosidase, and tyrosinase inhibition assays, respectively. The strong antioxidant effect was established by Lucknow-49 (IC50 of 74.43 ± 1.86 μg/mL) and Allahabad safeda (IC50 of 78.93 ± 0.46 μg/mL) for ABTS and DPPH assays, respectively. The ethyl acetate and methanolic leaf extracts of the Allahabad safeda cultivar showed better inhibition against Pseudomonas aeruginosa with an MIC of 14.84 and 28.69 µg/mL, respectively. A decent mean zone of inhibition was recorded in methanolic leaf extract that ranged from 21-25 mm in diameter against the tested bacterial strains (Proteus vulgaris, Bacillus subtilis, and P. aeruginosa). This is the first scientific report on the comparative and comprehensive analysis of indigenous guava cultivars to evidently shortlist the elite cultivars with enriched dietary nutrition and biological activities.